(untitled) (International Journal of Engineering Sciences & Management Research, 2016)
The main aim of this paper is to make a clear vision between the interrupt, trap and fatal error. Or we can say that the paper will be able to clarify the behavior and working of interrupt, trap and fatal error. This paper have justified definition and data about all these three terms ,and the paper itself is capable to differentiate and clear every confusion between these three terms called interrupt ,trap and fatal error.